The EMF: topics for discussion. A comment - PEETERS, T. (PSL Quarterly Review, 2013)
A comment on Tommaso Padoa-Schioppa’s paper The EMF: topics for discussion, presented at the Second International Seminar on European Economic and Monetary Union, held in Geneva in December of 1979. JEL: F33, F36